Análise dinâmica de torres estaiadas de linhas de transmissão submetidas à ruptura de cabo - Carlos, Thiago Brazeiro (2015)
The need for transmission lines expansion (TL) is evident in the face of growing electrical energy demand in Brazil as well as the great distances between generation and consumption centers. It is known that numerous failures can interrupt the energy transmission and the towers collapse is among the main reasons, causing huge losses to both electrical energy companies and final users. Thus, it is crucial to understand the mechanical behavior of these structures, considering the different actions that they can act so that the energy transmission can take place in a safe, efficient and economical way. In this context, this paper deals with the static and dynamic response evaluation of guyed lattice metallic towers of TLs submitted to broken conductor and broken lightning-rod cable. For this purpose, numerical models of isolated tower and completed stretch of TL were developed, including all components, towers, insulator chains, lightning-rod cables, conductor cables and prestressed stay cables. The models are subjected to static analysis through "equivalent static loads" application coming from the broken cable and dynamic analysis, in the time domain, using the method of direct integration of equations of motion explicitly, with central finite differences. The static and dynamic responses are given in terms of nodal displacements at the top and normal stresses in the tower bars. Finally, the results of the dynamic analysis in the time domain are compared with those determined by static analysis, employed in the usual design practice, that is, the peak and final values (after the structure stops vibrating) are compared with the static response values in order to verify the validity of the model used in the design practice.